Analysis of atmospheric vertical profiles in the presence of desert dust aerosols. (November 2015) - Costa, M J; Obregón, M A; Pereira, S; Salgueiro, V; Potes, M; Couto, F T; Salgado, R; Bortoli, D; Silva, A M
Abstract: The present work aims at studying a very recent episode of desert dust transport that affected Iberia in mid May 2015. The dust aerosols were detected over Évora, where a varied set of instrumentation for aerosol measurements is installed, including: a CIMEL sunphotometer integrated in AERONET, a Raman Lidar and a TEOM monitor, as well as ceilometer and a microwave radiometer (profiler). The aerosol occurrence, detected using the columnar, vertically-resolved and in situ measurements, was characterized by a fairly high aerosol optical thickness that reached a value of 1.0 at 440 nm and showed mass concentration peaks at the surface of the order of 100 μg/m 3 . Subsequently, the tropospheric vertical profiles of humidity and temperature obtained with the passive microwave (MW) radiometer are analysed in order to distinguish possible modifications that can be connected with the transport of desert dust. Modelling results are also examined and the total, SW and LW radiative forcings are investigated, taking into account the different vertical profiles obtained during the desert dust occurrence. It is found that the differences in the atmospheric profiles mostly affect the LW radiative forcing, with an underestimation of about 30% when the actual vertical profile is not considered.